ANALISIS KEAMANAN DATA TERHADAP PENGGUNAAN E-WALLET SEBAGAI ALAT TRANSAKSI DIGITAL UNTUK MENCEGAH PENIPUAN ONLINE - Laksamana Khaidir K.N; Muhammad Irwan Padli Nasution (JOURNAL SAINS STUDENT RESEARCH, 2024)
Technological developments have changed the way people shop in general, from previously retail shopping to online shopping, which is more efficient and practical. Data security in online shopping transactions is a crucial issue in the digital era which continues to develop rapidly. As consumer interest in shopping online increases, the popularity of e-wallets is also increasing among the public. However, the higher the public's interest in shopping online, the higher the risk of online fraud, especially in digital transactions. This research aims to analyze data security in online shopping transactions using e-wallets and develop strategies or ways to prevent online fraud.This research aims to analyze various aspects of data security in online shopping transactions and find out how this can prevent online fraud. The main objectives of this research are to identify common security threats, effective data protection techniques and methods, and implement security policies that increase consumer confidence in online transactions.The research method used is a literature review and secondary data analysis. The research results show that the e-wallet system is equipped with strong security mechanisms such as data encryption, user authentication, and transaction validation. However, risks remain if users do not follow good security practices, such as: For example, using secure devices, updating software, and watching out for phishing scams. Therefore, preventing online fraud in purchase transactions via e-wallets requires increased user awareness, strict security policies, and cooperation with governments, service providers, and the public.